2018
DOI: 10.2174/221068120701170419145428
|View full text |Cite
|
Sign up to set email alerts
|

Electronic, Thermochemistry and Vibrational Properties for Single-walled Carbon Nanotubes

Abstract: Background: The Single-wall Carbon Nanotubes (SWCNTs) represent one of the most active classes of nanostructures, and they have been widely used as active materials for important applications. In this study, the electronic, thermochemistry and vibrational properties of zigzag and armchair SWCNTs were investigated. Objective: Using these investigations, it is possible to obtain much more data to apply SWCNTs in medical science, industrial technologies and nanosensors applications. Methods: All the calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…102 The possible biochemical variations detected by nanobiosensors are associated with the thermochemistry of physiological reactions, such as endothermic or endothermic reactions that disturb systems and can be detected. 103 Moreover, it has been reported that variations and load distributions can generate changes in the electrical potential of the medium that can be detected. Nanobiosensors can also reveal oxy-reduction reactions.…”
Section: Biosensorsmentioning
confidence: 99%
See 3 more Smart Citations
“…102 The possible biochemical variations detected by nanobiosensors are associated with the thermochemistry of physiological reactions, such as endothermic or endothermic reactions that disturb systems and can be detected. 103 Moreover, it has been reported that variations and load distributions can generate changes in the electrical potential of the medium that can be detected. Nanobiosensors can also reveal oxy-reduction reactions.…”
Section: Biosensorsmentioning
confidence: 99%
“…The ion-selective electrodes based on the membrane or selective field effect, electrodes printed on canvas, electrodes modified through metal oxides, polymers. [93][94][95][96][97][98][99][100][101][102][103] Biosensors based on simple nanostructures such as metallic nanoparticles, even the most complex ones, such as spinel or perovskite structures, have an increasing application in detecting bio elements. These biosensors can also be based on the structures of graphene and its derivatives.…”
Section: Biosensorsmentioning
confidence: 99%
See 2 more Smart Citations
“…10, pp: ------ The arrow in the center of the molecule indicates the direction of the dipole moment of the active mode of vibration in the infrared spectrum]. And similarly to the single wall carbon nanotubes (SWCNs) [18,[23][24][25][26], the calculations of electronic charge for [7] Science, 2019, Vol. 60, No.…”
Section: Kubbamentioning
confidence: 99%